Wisata Alam Topa dan Kesejahteraan Masyarakat di Desa Labone Kecamatan Lasalepa Kabupaten Muna - Rismawati, Rismawati; Jalil, Abdul (JURNAL KABANTI: Kerabat Antropologi, 2025)
This research is entitled "Topa Natural Tourism and Community Welfare in Lobone Village, Lasalepa District, Muna Regency". The aim of this research is to determine the Topa Nature Tourism management system, and to determine the contribution of Topa Nature Tourism to the welfare of the Labone Village community. This research uses a qualitative descriptive method by collecting data by observing and interviewing. Data analysis by listening to interview results, writing interview transcripts, sorting data using ecotourism theory according to G Sudarto. The results of this research show that Topa Nature Tourism is managed by BUMDes administrators but is still allocated from village funds for infrastructure development, while the proceeds from levies go into the BUMDes treasury. Meanwhile, BUMDes administrators also maintain cleanliness, promote tourist attractions on social media, and arrange portal and parking schedules. Topa Nature Tourism's contribution to the community in Labone Village is expanding employment opportunities in the form of selling, renting tires and duck boats, and maintaining parking and portals so that it can increase the income of the people of Labone Village, Lasalepa District, Muna Regency